The Correlation Between Radiotherapy and Patients' Fear of Cancer Recurrence: A Systematic Review and Meta-analysis. Issue 3 (21st June 2022) - Zheng, Mimi; Wan, Hongwei; Zhu, Yu; Xiang, Lina
Abstract : The purpose of this review was to explore the correlation between patients' fear of cancer recurrence (FCR) and radiotherapy. National Knowledge Infrastructure, Wanfang Database, China Science and Technology Journal Database, SinoMed, PubMed, Web of Science, EBSCO-CINAHL, Cochrane Library, and Ovid Embase were searched to identify relevant studies. Thirty-five eligible studies were included in the systematic review, and 22 of them were included in further meta-analysis. The results of the meta-analysis showed that the level of patients' FCR was positively correlated with radiotherapy, but the correlation was weak (overall r = 0.075; 95% confidence interval [CI], 0.046-0.103; P = .000). In terms of subgroup analysis based on cancer site (breast cancer vs other types of cancer), the breast cancer group ( r = 0.086; 95% CI, 0.027-0.143; P = .004), the mixed-type group ( r = 0.073; 95% CI, 0.033-0.112; P = .000), and the other-type group ( r = 0.071; 95% CI, 0.015-0.126; P = .013) have a positive correlation with radiotherapy. Patients' FCR positively correlated with the receipt of radiotherapy. However, because of the variability among the studies, the results have limitations. Therefore, longitudinal studies are needed to verify the trajectory of FCR over radiation therapy.